Public knowledge of cardiovascular disease and its risk factors in Tangail, Bangladesh: a cross-sectional survey - Rahman, Masuder; Akter, Shakila; Zohora, Fatama Tous; Shibly, Abu Zaffar (International Journal Of Community Medicine And Public Health, 2019)
Background: Cardiovascular Disease (CVD) is a major public health problem throughout the world. In Bangladesh, the reliable data concerning various aspects of CVD is inadequate at present due to lack of national population-based surveys or central administrative health data. Given the rising incidence of CVDs in Bangladesh, an improved understanding of the CVD, symptoms and risk factors is needed. Hence, this study was performed to assess the level of knowledge towards CVD types, warning symptoms of heart attack or stroke, and CVD risk factors. Methods: A descriptive cross-sectional survey was conducted from May 2018 to June 2018 using standard questionnaire on a sample of 350 randomly selected Bangladeshi individuals. All the data of the study were input in SPSS (Statistical Package for the Social Sciences) version 20.0 software from IBM for windows and the gathered data thus analyzed using SPSS & Microsoft Excel. Results: The respondents’ knowledge about types of CVD, symptom heart attack, symptom of stroke and the risk factors of CVD are 38.9%, 67.7%, 35.7%, and 92.9% respectively. The most common risk factors of CVD found to be known by around than two-third of respondents were unhealthy diet (66.9%), physical inactivity (64.3), obesity (61.4%), and smoking (58.6%). Conclusions: The respondents’ knowledge about types of CVD, symptom heart attack, symptom of stroke and the risk factors of CVD are 38.9%, 67.7%, 35.7%, and 92.9% respectively. The most common risk factors of CVD found to be known by around than two-third of respondents were unhealthy diet (66.9%), physical inactivity (64.3), obesity (61.4%), and smoking (58.6%).